Cuba's foreign policy in global solidarity organizations : towards a revolutionary world order - Lassen, Lasse B. (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book analyzes the influence of the Cuban Revolutionary Government on the evolution of the Afro-Asian Peoples' Solidarity Organization (AAPSO). The author argues that Cuba's accession to AAPSO and the convocation of two solidarity conferences (1966/1967) in Havana initiated a political shift for the organization. The Cuban Revolutionary Government thus promoted the inclusion of Latin American delegations that represented their countries' leftist and pro-Cuban dissidence as well as rural guerilla movements. Adding to that, Fidel Castro's independent stance towards AAPSO's two main financers, the USSR and the PR China, fostered a gradual emancipation of the postcolonial organization from the dominance of its sponsors. The book offers a better understanding of the theoretical foundations of Cuba's foreign policy and explains how Havana used the two solidarity conferences to better the island's international prestige at times of diplomatic isolation. Retracing the diplomatic influence of a small but key diplomatic actor of the Cold War, this study will appeal to postcolonial and Latin America scholars, as well as to academic researchers in contemporary history and political sciences"--
Introduction : the Havana connection : analyzing Cuba's cold war network -- The international context (1955-1965) : AAPSO, decolonization, and the cold war -- The "Castro Doctrine" : shaping an antihegemonic foreign policy paradigm -- The Tricontinental Conference of Havana 1966 : the global Cuban Revolution -- The OLAS Conference of Havana 1967 : the apex of Latin American radicalism -- Conclusion : the Cuban Revolution's international paradigm -- Appendices. Delegates and observers at the Solidarity Conferences (1955-1967) -- Selection of tricontinental posters.
Keywords: Permanent Organization for Afro-Asian Peoples' Solidarity; Organization of Latin American Solidarity. -- Conference -- 1967 : -- Havana, Cuba); Cuba -- Foreign relations -- 1959-1990.; Cuba -- Foreign relations -- Developing countries; Developing countries -- Foreign relations -- Cuba; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General